Du cadre d’action collective au programme partisan : ancrages patronaux des islamismes en Turquie et en Tunisie - Dilek Yankaya (L’Année du Maghreb)
This article explores how economic representations of Islamist parties are constructed through the prism of the relations of militant networks to the economy. The analysis focuses on Ennahdha in Tunisia and the Justice and Development Party in Turkey, whose programs are seen to bring no model of alternative development and to make the Islamic reference an element of rhetoric. Instead of evaluating the failure or success of these movements by the influence of a religious orthodoxy, the text focuses on the framing work carried out by partisan groups in interaction with their social properties and according to specific temporalities and scales of action. After having shown how the differences in socio-economic implantation of the Turkish and Tunisian Islamist movements reveal the divergences in the modalities of the politicisation of the economy, the article indicates that once mobilised, the partisan businessmen occupy a front seat place in the movement as actors of the materialisation of its framework, made possible by their multipositionality.